Evaluasi Kebijakan Perlindungan Lahan Pertanian Perda Kabupaten Pati No 2 Tahun 2021 Dalam Mengendalikan Alih Fungsi Lahan Pertanian di Kabupaten Pati - Girindra Sri Ayu Kusuma Djanabadra; Supratiwi Supratiwi (Journal of Politic and Government Studies, 2026)
The conversion of agricultural land in Pati Regency, particularly in Juwana District, has the potential to threaten the existence of Sustainable Food Agricultural Land (LP2B) and regional food security. This study aims to evaluate the implementation of Pati Regency Regulation No. 2 of 2021 on controlling the conversion of sustainable food agricultural land and identify inhibiting factors in its implementation. This study used a qualitative method with a descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation. The results indicate that policy implementation is not yet fully optimal. Although administratively protected land areas have been determined, land conversion still occurs at the implementation level due to pressure from industrial and residential development. The main inhibiting factors include weak supervision, suboptimal coordination between regional agencies, the dominance of economic interests, and limited incentive instruments for agricultural land owners. This study recommends that the Pati Regency Government strengthen the synchronization of spatial planning and agricultural land protection policies, improve licensing oversight and transparency, and develop more effective incentive and disincentive instruments. Further research is recommended to examine the dynamics of conflicting interests between the agricultural and industrial sectors in regional development planning, thereby establishing a more balanced policy formulation between economic growth and agricultural land protection.